AB0155 Microrna-155 Mediates Augmented Cd40 Expression in Lupus Plasmacytoid Dendritic Cells. (15th July 2016) - Sheng, Y.; Yim, A.L.Y.; Tam, R.C.Y.; Chan, A.; Lu, L.; Lau, C.S.; Chan, V.S.F.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic multi-organ autoimmune disease characterized by hyperactivated immune responses to self and persistent systemic inflammation. In addition to autoreactive T and B cells, dendritic cells also play an important role in inducing inflammation. Previously, we have reported abnormalities in circulating and bone marrow (BM)-derived plasmacytoid dendritic cells (pDCs) from SLE patients which suggested that pDCs may play a role in mediating SLE pathogenesis 1–3 . Objectives: In this investigation, we aim to seek for potential regulators that mediate functional aberrations of pDCs in SLE. Methods: Bone marrow-derived pDCs from NZB/W F1 mice before and after the disease onset were compared for costimulatory molecule expressions and toll-like receptor (TLR) 7 stimulated responses. TLR7-induced microRNA (miRNA) profile changes in pDCs were examined to identify specific miRNA regulator. Functional validation of specific miRNA was further studied by transfection of miRNA mimics. Results: In vitro derivation of pDCs from BM of pre-symptomatic and symptomatic NZB/W F1 mice showed similar basal expression of co-stimulatory molecules and TLRs -7 and -9. Functionally, symptomatic pDCs exhibited hypersensitivity to TLR7 but not TLR9 stimulation, as represented by the elevated upregulation of CD40, CD86 and MHC class II molecules upon R837 stimulation. In miRNA profiling, a significantly higher induction of miR-155 in symptomatic pDCs following TLR7 stimulation was observed. The transfection of miR-155 mimics in pre-symptomatic pDCs induced an augmented expression of Cd40 which is consistent with the increased CD40 expression in symptomatic pDCs. Cd40 expression was also found to negatively correlate with the miR-155 target Ship1 in pDCs. Conclusions: Overall, results from the current study provide evidence for miR-155-mediated regulation in pDC functional abnormalities in SLE. Findings from this study contribute to a better understanding of SLE pathogenesis and ignite future interests in evaluating the molecular regulation in autoimmunity. References: Jin, O., et al., Systemic lupus erythematosus patients have increased number of circulating plasmacytoid dendritic cells, but decreased myeloid dendritic cells with deficient CD83 expression. Lupus. 2008;17(7):654–62 Jin, O., et al., Abnormalities in circulating plasmacytoid dendritic cells in patients with systemic lupus erythematosus. Arthritis research & therapy. 2010;12(4):R137 Nie, Y.J., et al, Phenotypic and functional abnormalities of bone marrow-derived dendritic cells in systemic lupus erythematosus. Arthritis research & therapy. 2010;12(3):R91. Acknowledgement: Hong Kong Research Grant Council General Research Fund (770213) Disclosure of Interest: None declared